Scientometric Analysis of Knowledge in the Context of Project Management: Subject Area: (Knowledge Management and Project Management) - Rincón-González, César; Díaz-Piraquive, Flor Nancy (Knowledge Management in Organizations, 2019)
This research work carried out a meticulous scientometric analysis about the knowledge management in the context of project management, in order to build a detailed state of the art about the matter of study, allowing the identification of main elements investigated on the scientific literature about the knowledge on this context. Firstly; a theoretical framework was build, allowing the identification of concepts about knowledge management and scientometric analysis. Secondly; a methodology was constructed, by integrating analytics and measurement tools, 881 publications related to the knowledge management on projects were identified on the main databases, later, detailed bibliometric analysis were conducted in order to highlight the most investigated topics, main authors (Gemino, Carrillo and Reich) and sources with higher amount of documents and quotes on the scientific literature about the matter of study (International Journal of Project Management, Project Management Journal and Journal of Knowledge Management). Afterwards; the results of the scientometric analysis about the knowledge on projects were documented. And finally; conclusions were established and as future lines of research were identified the impact of knowledge management on project performance, leadership, management, and innovation.